Incubación posruminal de bolsas móviles de nylon mediante una sonda de incubación abomasal (2010)
In order to carry out studies of postruminal digestibility in animals with ruminal cannula, it was developed a technique based on incubation of mobile nylon bags (MNB) in the abomasum by means of a tube that is inserted through the ruminal cannula. To develop the technique and evaluate the effectiveness of abomasal incubation tube (AIT) five trials were performed to test probes with different diameters, and MNB with different sizes, kinds of foods and sample weight. Although the technique is simple, easy to perform and safe for animals, the recovery of NMB with food samples is less than 40% after 120 hours of incubation being necessary its adjustment to improve the percentage of recovery and reduction of the the time of collection of NMB.